Vitex negundo Linn.: phytochemical composition, nutritional analysis, and antioxidant and antimicrobial activity - Koirala, Niranjan; Dhakal, Chiran; Munankarmi, Nabin Narayan; Ali, Shinawar Waseem; Hameed, Aneela; Martins, Natália; Sharifi-Rad, Javad; Imran, Muhammad; Arif, Atta Muhammad; Hanif, Muhammad Shakeel; Basnyat, Ram Chandra; Salehi, Bahare (Cellular and Molecular Biology, 2020)
Vitex negundo (VN) is a widely used plant in folk medicine, namely for the treatment of jaundice, wounds, body ache, toothache, asthma, eye pain, and migraine. These effects have been increasingly attributed to its chemical composition. Here, we assessed the VN chemical and nutritional composition and biological activity, with particular emphasis on antioxidant and antimicrobial effects. VN methanol and hexane extracts revealed the presence of important phytochemical, such as terpenoids, polyphenol, steroids, saponins, phenolic compound and flavonoids. Total phenolic content of VN methanol extract from bark was 1082.473 mg/g GAE and that of leaves was 1382.984 mg/g GAE. The total flavonoids content in VN methanol extract from VN bark was 127.744 mg/g QE and that of leaves was 123.776 mg/g QE. VN methanol extract from bark exhibited high antioxidant effects (IC50=38.47 ppm). The content (%) of ash, moisture, crude fiber, crude protein and fat in VN leaves was, respectively, 7.86%, 18.35%, 6.52%, 9.687% and 6.19%. VN leaves methanol extract revealed antimicrobial activity against Bacillus subtilis and Staphylococcus aureus, with inhibition halos being, respectively, 13 mm and 14 mm, and the MBC values were found to be 1.562 mg/mL and 6.25 mg/mL, respectively. Similarly, VN bark methanol extract led to inhibition halos of 18 mm and 15 mm for B. subtilis and S. aureus, respectively, and the MBC values were found to be 2.372 mg/mL and 0.245 mg/mL. GC-MS analysis of the VN bark methanol extract revealed that monoolein was the major compounds, with an area of 0.57%. Thus, our results encourage the potential use of VN as a medicinal product, with high protein contents, and prominent antioxidant and anti-bacterial effects.